Evaluating academic agency components on the web - Castañeda Figueiras, Sandra (Consorcio de Universidades Mexicanas A.C., 2014)
It is argued the need to reform structures and forms of organization at the national universities to meet the challenges of a changing world where developments in science and technology demanded that the university offer increasingly more qualified and to respond to the challenge of developing knowledge and skills for lifelong learning. In particular, where individuals show to be autonomous and responsible for be agents that intentionally make things happen, from their actions. Thus, understanding the role that play the systems of beliefs about knowledge (whether epistemological or not), much as understanding the mechanisms that use the cognitive heuristics and self-regulating responsible for university learning, constitutes a central evaluation focus and intervention in higher education, so that you can help students to exercise his personal influence in the performance of an active role in their self-development. Based on this sense of academic agency, the article offers a global perspective on it and describes the development, calibration and validation of standardized artifacts to evaluate both cognitive mechanisms (beliefs and cognitive heuristics), self-regulation (causal and motivational), insofar as they constitute core components in determining the quality of complex agentive nature learning. Finally, is the development of an evaluative tool on web that enhances the impact of the presented technological derivatives by extending the benefits of web applications to diagnosis and foster cognitive development and complex learning. In this context, further developments in learning supported by mobile technology will be cognitive artifacts responsible for promoting them.